Modulation of immunogenicity of poly(sarcosine) displayed on various nanoparticle surfaces due to different physical properties. (7th November 2017) - Kim, Cheol Joo; Hara, Eri; Watabe, Naoki; Hara, Isao; Kimura, Shunsaku
Abstract : Poly(sarcosine) displayed on polymeric micelle is reported to trigger a T cell‐independent type2 reaction with B1a cells in the mice to produce IgM and IgG3 antibodies. In addition to polymeric micelle, three kinds of vesicles displaying poly(sarcosine) on surface were prepared here to evaluate the amounts and avidities of IgM and IgG3, which were produced in mice, to correlate them with physical properties of the molecular assemblies. The largest amount of IgM was produced after twice administrations of a polymeric micelle of 35 nm diameter (G1 ). On the other hand, the production amount of IgG3 became the largest after twice administrations ofG3 (vesicle of 229 nm diameter) orG4 (vesicle of 85 nm diameter). The augmented avidity of IgG3 after the twice administrations compared with that at the single administration was the highest withG3 . These differences in immune responses are discussed in terms of surface density of poly(sarcosine) chains, nanoparticle size, hydrophobic component of poly(L‐lactic acid) or (Leu‐ or Val‐Aib)n, and membrane elasticity of the nanoparticles. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The immune responses of IgM and IgG productions triggered by 4 kinds of nanoparticles displaying the same antigen of poly(sarcosine) on surface were studied. IgM production and class‐switching were differently influenced by the physical properties of surface density of poly(sarcosine) chains, nanoparticle size, hydrophobic component of the constituents, and membrane elasticity of the nanoparticles.